John Caird on Shakespeare: An Interview. (3rd April 2022) - Shepherd, Scott
ABSTRACT: British director John Caird's career spans six decades. In addition to work at the National Theatre and the Royal Shakespeare Company, he has directed numerous productions of drama, opera and musical theatre in the UK, Japan, Sweden and elsewhere. He directed Hamlet in English at the UK's National Theatre in 2000, and in Japanese at the Tokyo Metropolitan Theatre in 2017. In this 2021 interview, Caird tells Scott Shepherd about his philosophy for directing Shakespeare, as well as the way he approached Hamlet, the challenges of directing in Japanese and Swedish, and more. 1